Pediatric-Specific Hazard Vulnerability Analysis: The Missing Component of Regional and Hospital-Based Preparedness. (30th May 2023) - Kappy, Brandon; Parish, April; Barda, Amie; Frost, Pat; Timm, Nathan
Abstract: Though children comprise a large percentage of the population and are uniquely vulnerable to disasters, pediatric considerations are often omitted from regional and hospital-based emergency preparedness. Children's absence is particularly notable in hazard vulnerability analyses (HVAs), a commonly used tool that allows emergency managers to identify a hazard's impact, probability of occurrence, and previous mitigation efforts. This paper introduces a new pediatric-specific HVA that provides emergency managers with a quantifiable means to determine how a hazard might affect children within a given region, taking into account existing preparedness most relevant to children's safety. Impact and preparedness categories within the pediatric-specific HVA incorporate age-based equipment and care needs, long-term developmental and mental health consequences, and the hospital and community functions most necessary for supporting children during disasters. The HVA allows emergency managers to create a more comprehensive assessment of their pediatric populations and preparatory requirements.